Monitoring Drought in the Lake Urmia Basin Using Global Precipitation Data - Ahmad Ebrahimpour, Edris (Management Strategies and Engineering Sciences, 2026)
This study investigates the drought status in the Lake Urmia basin using the Standardized Precipitation Index (SPI) and the Standardized Precipitation-Evapotranspiration Index (SPEI) under current and climate change conditions. To monitor past drought events, observational data and precipitation records from global databases—namely CRU, GPCC, and UDEL—were utilized. The results of drought monitoring revealed that severe droughts occurred in the basin during the years 1989, 1991, between 1999 and 2001, and in 2008. Moreover, the evaluation of precipitation datasets for drought monitoring showed that the GPCC database performed best, followed by CRU and UDEL, respectively. Furthermore, to forecast future droughts, a hybrid model combining Support Vector Regression (SVR) and Genetic Algorithm (GA-SVR) was employed. The drought forecasting results indicated that prediction accuracy increases with the extension of the SPI calculation scale, whereas it decreases as the forecast lead time increases. To evaluate future droughts, outputs from 29 General Circulation Models (GCMs) were combined under both the optimistic RCP 2.6 and pessimistic RCP 8.5 scenarios. The evaluation of the hybrid model output demonstrated that temperature in the basin is projected to increase under both scenarios, while precipitation is expected to rise under the optimistic scenario and decrease under the pessimistic scenario. Future drought monitoring based on the SPI revealed that drought frequency will not significantly increase. However, the SPEI results indicated a statistically significant rise in the number of future drought events. The findings suggest that temperature will play a critical role in future drought occurrences. For instance, based on the nine-month SPEI, 12 severe drought events were recorded during the baseline period, whereas under the RCP 2.6 scenario, the number of events is projected to increase to 18, 19, and 19 during the near future (2011–2040), mid-century (2041–2070), and far future (2071–2100), respectively. Under the RCP 8.5 scenario, the corresponding figures are expected to rise to 21, 28, and 38 events, respectively.